2021
DOI: 10.1002/edm2.257
|View full text |Cite
|
Sign up to set email alerts
|

Glucose patterns following alcohol and illicit drug use in young adults with type 1 diabetes: A flash glucose monitoring study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…When considering the dangers associated with alcohol along with non-disclosure of emergency situations to HCPs, there is a likely underestimation of the prevalence of severe glucose episodes. 7,20 Our study also demonstrated this with participants highlighting lack of honesty with alcohol 'stories' to their diabetes HCPs, or not disclosing any episodes for fear of being told off, and judged. Non-disclosure of severe hypoglycaemia linked to driving restrictions may also be the cause.…”
Section: Non-disclosuresupporting
confidence: 54%
See 2 more Smart Citations
“…When considering the dangers associated with alcohol along with non-disclosure of emergency situations to HCPs, there is a likely underestimation of the prevalence of severe glucose episodes. 7,20 Our study also demonstrated this with participants highlighting lack of honesty with alcohol 'stories' to their diabetes HCPs, or not disclosing any episodes for fear of being told off, and judged. Non-disclosure of severe hypoglycaemia linked to driving restrictions may also be the cause.…”
Section: Non-disclosuresupporting
confidence: 54%
“…With glycaemic symptoms and blood alcohol concentration symptoms being comparable (increased confidence, giggling, polyuria, boisterous/loud behaviour, loss of co‐ordination, slurred speech, confusion, nausea and vomiting, loss of consciousness), 19 this is understandable. This link between the feelings of being drunk and hypoglycaemia/hyperglycaemia may be helpful in future patient education regarding cognition and increasing blood glucose awareness, which is only possible by physically testing, scanning or checking an insulin pump connected to continuous glucose monitoring 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have provided evidence for the correlation between alcohol consumption and glycemic control ( 40 , 41 ) proving that alcohol consumption is an additional disadvantage in the long-term therapy of T1D patients.…”
Section: Discussionmentioning
confidence: 99%